Parental Support as a Correlate of Psychological Well-being of In-School Adolescents in Central Lagos, Nigeria - Omoshalewa Lasbat Badanas (Faculty of Social Science, Universitas Negeri Semarang, 2023)
This study is a descriptive design of the survey type which is aimed at assessing parental support and in-school adolescents’ psychological well-being in Central Lagos. The population for this study comprises all upper basic school students in Central Lagos from which 200 students were selected from 10 upper basic schools in Central Lagos. An adapted questionnaire was used to gather data for this study. Research questions 1 and 2 were answered using frequency count and percentage while the research hypothesis was tested using Pearson Product Moment Correlation at a 0.05 level of significance. Findings revealed that the level of parental support of in-school adolescents in Central Lagos was high. The level of psychological well-being among in-school adolescents was low. There is a significant relationship between Parental support and psychological well-being in Central Lagos. Based on the findings, it was therefore recommended that parents should give adolescents support that will allow for positive interaction. Also, parents should give adolescents support that will improve their well-being. Parental support should not be too extreme so that it will not hamper adolescents' psychological well-being.